Aplikasi Manajemen Service Kendaraan Bermotor Menggunakan Teknologi QR Code - Hasriani Hasriani; Hardi Hardi; Suryani Suryani; Faizal Faizal (Jurnal Pendidikan Tambusai, 2023)
Motor vehicle service management, especially cars in a company, has a service flow that takes up a lot of time. In general, the customer checks the vehicle, buys spare parts to be brought to the mechanic for service, then makes a payment transaction. Likewise, when performing certain car body parts services, the mechanic sets the service price until the payment transaction. In the service process, if another damage is found, the car company must confirm with customers who are at the service center or outside via cell phone. Furthermore, the customer repeats the transaction so that the car service process takes longer. Customers who are at the service location must spend more time waiting for the service to finish. This research aims to create a car service management application using QR Code technology, by creating a mechanism between spare parts sales departments, mechanics, and cashiers. This application can make it easier for customers to monitor the types of damage and services needed, the status of car services, prices of spare parts, and service fees that are completed to be done. By scanning the QR Code, customers can remotely monitor car service, making it easier and more efficient.